Peningkatan Prestasi Belajar IPS Melalui Model Pembelajaran STAD Berbantuan Media Kartu Bergambar pada Siswa Kelas IV Sekolah Dasar - Rina Rusita; Muhammad Hanif; Sudarmiani Sudarmiani (Universitas PGRI Semarang, 2020)
This study aims to improve students’ social sciences learning achievement for fourth-grade students at the state elementary school of Campursari, Sambit, Ponorogo regency in the academic year 2019/2020. The subject lesson on students’ tasks through the STAD learning model (student teams-achievement divisions) assisted by pictorial card media. The research design was used as a qualitative-quantitative method or mixed-method. This type of research commonly called classroom action research which consisted of three cycles. The research subjects were 20 students from fourth-grade students. The instruments were used conducting observation, tests, and documentation techniques. To collect the data, I used observation sheets of STAD model learning implementation, student activity observation sheets, group activity widths, and post-test questions. The results showed that the use of the STAD learning model assisted by the pictorial card media definitely can improve the students’ social sciences learning achievement of fourth-grade students. This enhancement is witnessed by the increasing of the average score of pre-cycle learning achievement from 60 increased to 73.50 in the first cycle, then increased 85.25 in the second cycle, finally increased up to 88.75 in the third cycle. The percentage of pre-cycle learning achievement from 40% increased to 75% in the first cycle, then increased to 85.25% in the second cycle, finally increased again until 100% in the third cycle. The writer states that the application of the STAD learning model assisted by the pictorial card media absolutely can improve the students’ social sciences learning achievement.